Respostas
respondido por:
3
(a1 + a9)/2 = a5
(6 + 46) / 2 = 26=(a5)
(a1 + a5) / 2 = a3
(6 + 26) / 2 = 16=(a3)
(a1 + a3) / 2 = a2
(6 + 16) / 2 = 11=(a2)
a2 - a1 = r
11 - 6 = 5
A razão é 5
então ficará: 6, 11, 16, 21, 26, 31, 36, 41, 46.
(6 + 46) / 2 = 26=(a5)
(a1 + a5) / 2 = a3
(6 + 26) / 2 = 16=(a3)
(a1 + a3) / 2 = a2
(6 + 16) / 2 = 11=(a2)
a2 - a1 = r
11 - 6 = 5
A razão é 5
então ficará: 6, 11, 16, 21, 26, 31, 36, 41, 46.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás